Report on the Geological Field Trip to Mahakam Delta and Balikpapan Bay (August 31st to September 4th, 2018), Organized by FOSI-IAS-SEPM as Part of Regional Seminar: Past & Present Sedimentation in Tropical Region - Tri Handayani (Berita Sedimentologi, 2019)
The Mahakam Delta and Balikpapan Bay Field Trip was held on August 31st to September 4th, 2018 and lead by Dr. Erlangga Septama (G and G Advisor for Pertamina EP asset 5 at that time). Pertamina EP Asset 5 has carried out several fieldworks in the Mahakam Delta, Balikpapan Bay and surrounding area since 2013 to improve the understanding of subsurface reservoir geometry, internal architecture and potential sand connectivity in a less constrained style (e.g. surface outcrop vs. core or wireline log data). The study, as also our field trip; aimed to characterize the facies and stratigraphy of the deltaic sequence from outcrops and correlates them to the subsurface data in Sangasanga Field. This field based study is required to fill the knowledge gap due to the scarcity of the subsurface data in the existing oilfields.